An Analysis of Grammatical Errors in Writing Paragraph made by Eleventh Grade Students of Accounting in SMK N 1 Jambi Academic Year 2017/2018 - Novita Debora, Wennyta, Nurul Fitri (JELT: Journal of English Language Teaching, 2018)
AbstractThis research aimed to find outtypes  of grammatical errors  in writing paragraph based on surface strategy taxonomy made by eleventh grade students of accounting in SMK N 1 Jambi. This research used qualitative method. This research involved 35 students of Accounting IV in SMK N 1 JAMBI academic year 2017/2018 and choosing them by using random sampling technique. The data were collected through test. In this research, the reseacher used classification of  errors based on Dulay’s theory. The findings show that students  committed error  into  four  types:  omission,  addition,  misformation,  and misordering. From  the frequency  of  each  error  types, misformation was the error which most frequently produced by the students. It took 44,70 % of the total errors. Moreover, 32,94 % errors fell into error of omission and 15,29 % errors fell into misordering; whereas, for addition, it only took 7,05 %.Keywords: Grammatical Error, Writing, Paragraph